Interaction potential between vortex lines for uniaxial superconductors in the London approximation - Sardella, Edson [UNESP] (American Physical Society (APS), 1996)
Two distinct expressions of the interaction potential between arbitrarily oriented curved vortex lines with respect to the crystal c axis are derived within the London approximation. One of these expressions is used to compute the eigenvalues of the elasticity matrix. We examine the elastic properties of the vortex chain lattice, recently proposed, concerning shearing deformation.